Effect of Freeze-Drying on Apple Pomace and Pomegranate Peel Powders Used as a Source of Bioactive Ingredients for the Development of Functional Yogurt - Munir Ahmed; Anwar Ali; Aleena Sarfraz; Qin Hong; Hu Boran (Journal of Food Quality)
Agro-industrial by-products of fruits have turned into an essential source of bioactive products. This study examined the effect of freeze-drying on apple pomace powder (APP) and pomegranate peel powder (PPP) and their utilization in functional yogurt development at different concentrations. Freeze-dried powders in functional yogurt were investigated by chemical profile and bioactive characterization of total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. The highest concentration of TPC (4.64) mg GAE/g, TFC (1.73 ± 0.00) CE mg/g, and antioxidant activity (83.87 ± 0.02) % was investigated in the yogurt sample T6, having the maximum amount of PPP in it, which was significantly higher compared to the treatments having APP. Yogurt samples were analyzed for their sensory attributes, which showed a decline with the increase in both APP and PPP concentrations in contrast by introducing the optimum levels of APP and PPP (3% or 6%); hence, no significant loss in sensory profile was found as compared to the control samples. The results were found to be significant at the level (p<0.05). In terms of the freeze-dried APP and PPP results, the APP samples had the most complete chemical composition, with the exception of fiber and ash concentration. Treatments of functional yogurt were prepared for their physicochemical profile, which demonstrated a straight proportionate relationship between the proportions of both powders in the meantime. Protein and fat levels were likely to decrease as both dry powder levels increased. Hence, apple pomace and pomegranate peel can be used after freeze-drying as a rich source of bioactive compounds in functional yogurt in the food industry.